The Use of Type D and Type F Admixtures Concrete and Their Effects on Setting Time and Compressive Strength - Abdul Fatah; Akmala Rafi Prasetia; Asep Dudi; Muhammad Afif SM; Laode Azan Muzahab (Journal of Social Research, 2025)
The challenges of concrete usage in Indonesia, such as hot weather, remote construction sites, and improper manual casting practices, often lead to reduced concrete quality due to excessive water addition. This study investigates the effects of Type D (*Sika-Plastiment-83am*) and Type F (Sikament-LN) admixtures on concrete's setting time and compressive strength to address these issues. The research aims to optimize admixture dosages (0.2%, 0.25%, and 0.3% by cement weight) to enhance concrete performance while adhering to SNI and ASTM standards. Methods included literature reviews, field studies, and laboratory tests, such as slump tests, compressive strength tests (at 7, 14, and 28 days), and initial setting time measurements using penetrometers. Findings revealed that admixtures significantly improved compressive strength (31.6–34.0 MPa, exceeding the 30.0 MPa target) and extended initial setting times (3 hours 45 minutes to 5 hours 10 minutes) compared to untreated concrete (2 hours 20 minutes). The optimal dosage balanced workability (slump: 12±2 cm) and delayed hardening, ensuring suitability for casting. The study concludes that admixtures effectively replace water addition, enhancing strength and workability while mitigating premature drying. Practical implications include recommendations for admixture use in hot climates and remote projects to maintain concrete quality and durability.